158k views
2 votes
Simply this expression (3 + 2i)^2

User Tempranova
by
5.6k points

2 Answers

4 votes

Answer:

5 + 2i

Explanation:

since
√(-1) = i

Use the perfect square formula ( a + b )^2

= 3^2 + 2 · 3 · 2i + (2i)^2

= 5 + 2i

or,


5+2√(-1)

User Hypheni
by
5.4k points
3 votes

Answer:

5 + 12i

Explanation:

(3 + 2i)^2 = (3 + 2i)(3 + 2i) = 9 + 6i + 6i + 4i^2 = 9 + 12i - 4 = 5 + 12i

User Desiree
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.